2014
DOI: 10.1039/c4ra05052e
|View full text |Cite
|
Sign up to set email alerts
|

A microgripper sensor device capable of detecting ion efflux from whole cells

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In other work reported previously, we have modelled and experimentally verified the heat loss mechanism in the microgripper [16], performed further heat loss studies in different ambient gases over a range of pressures [17] and demonstrated the use of the microgripper in holding a cell while simultaneously being able to detect and quantify the excretion of potassium ions using an ion specific electrode fabricated as an integral part of the structure [18].…”
Section: Introductionmentioning
confidence: 99%
“…In other work reported previously, we have modelled and experimentally verified the heat loss mechanism in the microgripper [16], performed further heat loss studies in different ambient gases over a range of pressures [17] and demonstrated the use of the microgripper in holding a cell while simultaneously being able to detect and quantify the excretion of potassium ions using an ion specific electrode fabricated as an integral part of the structure [18].…”
Section: Introductionmentioning
confidence: 99%